Feasibility study and system design for small scale integrated renewable energy supply for UiTM Penang guard house employing the use of PV source / Nur Fazira Haris - Haris, Nur Fazira (2008)
A stand-alone Photovoltaic (PV) system is design to operate residential appliances such as fluorescent lights, ceiling fan, or even air conditioner. This paper presents two methods in determine the size of solar array and battery bank for stand alone PV system, there are (i) Conventional approach and (ii) Loss of power supply probability (LPSP) approach, under a given load at the UiTM Guard House. A computer program has been developed to size the system components (PV module and battery bank) in order to match the load at the site in most cost effective way. This paper also include propose of the type of installation of the PV system.